SCIENCE AND MATHEMATICS TEACHERS’ COMPETENCY IN EVALUATING STUDENTS’ AFFECTIVE AND PSYCHOMOTOR DOMAINS OF SENIOR SECONDARY CLASSROOM INSTRUCTION IN BENUE STATE (UNIZIK Journal of STM Education, 2024)
This was a study on science and Mathematics teachers’ competency in evaluating students’ affective and psychomotor domains of senior secondary classroom instruction in Benue State. Four research questions and four null hypotheses were formulated to guide the study. Descriptive survey design was used. Population comprised all Science and Mathematics teachers in Makurdi LGA of Benue State. Sample consisted of 104 (78 Science and 26 Mathematics) teachers in 26 senior secondary schools obtained using multi-stage sampling. Validated Science and Mathematics Teachers Competence in Evaluating Classroom Instruction Questionnaire (SMTCECIQ) constructed by the researchers had reliability coefficient of 0.89 computed using Cronbach alpha. Data obtained were analyzed using mean and standard deviation to answer the research questions and Independent sample t- test to test the formulated null hypotheses at 0.05 level of significance. Results showed: significant difference in the mean ratings of science and Mathematics teachers’ competency to objectively evaluate science students’ affective area during classroom instruction; No significant difference in the mean ratings of science and Mathematics teachers’ competency to objectively evaluate science students’ psychomotor area during classroom instruction; No significant difference in the mean ratings of science and Mathematics teachers’ competency to objectively evaluate science students’ affective and psychomotor areas during Mathematics classroom instruction. The study recommended among others that, science teachers Association and Mathematics Association of Nigeria should frequently organise conferences, seminars and workshops and encourage teachers to attend in order to increase their knowledge and skills to objectively evaluate students’ affective and psychomotor areas.
Keywords: Evaluation, teachers’ competences, science and Mathematics, STEM